2019
DOI: 10.1016/j.isatra.2018.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Bayesian networks for fault isolation: A diagnostic case study of diesel fuel injection system

Abstract: Fault isolation is known to be a challenging problem in machinery troubleshooting. It is not only because the isolation of multiple faults contains considerable number of uncertainties due to the strong correlation and coupling between different faults, but often massive prior knowledge is needed as well. This paper presents a Bayesian network-based approach for fault isolation in the presence of the uncertainties. Various faults and symptoms are parameterized using state variables, or the so-called nodes in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Considering the very high accuracy of the developed ANN on this task, the authors concluded that, compared to traditional methods based on signal analysis techniques and shallow classifiers, their approach can automatically learn high-level representative features from the raw vibration signals and eliminate the necessity of the time-consuming manual feature extraction. A similar study was performed by the authors of Wang et al (2019) presenting a Bayesian ANN-based approach for fault isolation in a DE fuel injection system under the presence of uncertainties. With the proposed approach, the authors demonstrated that symptoms under multiple faults could be decoupled into symptoms correspond-ing to each individual fault.…”
Section: Data-driven Modelsmentioning
confidence: 79%
“…Considering the very high accuracy of the developed ANN on this task, the authors concluded that, compared to traditional methods based on signal analysis techniques and shallow classifiers, their approach can automatically learn high-level representative features from the raw vibration signals and eliminate the necessity of the time-consuming manual feature extraction. A similar study was performed by the authors of Wang et al (2019) presenting a Bayesian ANN-based approach for fault isolation in a DE fuel injection system under the presence of uncertainties. With the proposed approach, the authors demonstrated that symptoms under multiple faults could be decoupled into symptoms correspond-ing to each individual fault.…”
Section: Data-driven Modelsmentioning
confidence: 79%
“…A similar study was performed in Wang et al (2019), in which the authors presented a Bayesian network-based approach for fault isolation in a DE fuel injection system, under the presence of uncertainties. Special consideration was given in the simplification of the Bayesian network structures, due to which symptoms under multiple faults could be decoupled into symptoms corresponding to each individual fault.…”
Section: Ddmsmentioning
confidence: 91%
“…According to [2,[27][28][29], networks are considered the most powerful fault diagnosis techniques and have been widely used in various fields, such as mine seismic event discrimination [30,31], and some works considering intrusion detection in wireless communication networks, which could also be helpful in fault localization [32]. Bayesian network techniques are also widely used in mechanical equipment [33][34][35], electronic equipment [36,37], thermal power plants [38,39], petrochemical plants [40,41], nuclear power plants [42,43], and medical diagnoses [44][45][46].…”
Section: Related Workmentioning
confidence: 99%